Diagnosis of Heartworm (Dirofilaria immitis) Infection in Dogs and Cats by Using Western Blot Technique - Tawin Inpankaew; Burin Nimsuphan; Kiattchai Rojanamongkol; Chanya Kengradomkij; Sathaporn Jittapalapong (Agriculture and Natural Resources, 2006)
Heartworm (Dirofilaria immitis) infection is the causative parasite of severe disease in dogs and cats. This mosquito-borne parasite is also found in wild animals and occasionally evident in humans. Diagnosis of dirofilariasis in companion animals is mainly performed by modified Knott’s technique and commercial serological tests. The objective of this study was to develop an alternative diagnosis of heartworm infections in pet animals. Blood samples of dogs and cats were collected and demonstrated the heartworm infection. Somatic proteins of nematodes such as D. immitis, Toxocara canis, T. cati, Ancylostoma ceylanicum and A. caninum were used to compare the protein profiles by using polyacrylamide gel electrophoresis (PAGE). The sera of heartworm-infected animals were used in detection of antigens associated with D. immitis proteins by Western blot (WB) analysis. WB results revealed that somatic antigens of D. immitis contained seven major peptide bands from 25 to 250 kDa recognized by the sera of infected dogs and three bands from 33 to 64 kDa recognized in cats. There were cross-reacted protein bands (50 and 64 kDa) found in all nematodes. The protein at 33 kDa was unique since it was only demonstrated by heartworm infected dog and cat sera. WB results indicated that this technique might be considered as the alternative diagnosis for heartworm infection.